(untitled) (Asian Journal of Medical Sciences, 2019)
Background: Human umbilical cord Wharton’s jelly (hUCWJ) derived Mesenchymal stem cells (MSCs) is a non-controversial, easily available source of human tissue which has a close association with embryonic tissue. Explant culture technique of isolating MSCs do not require any proteolytic enzymes giving an edge when compared to enzymatic methods. Aims and Objective: This study was designed to develop a suitable protocol to optimize the number of primary cells by transferring the explants after a successful migration and before trypsinizing of MSCs from primary culture plate to new culture plates. Materials and Methods: For defining the isolated cells as MSCs, the cells were studied by colony forming assay, semiquantitative two steps reverse transcriptase polymerase chain reaction (RT-PCR) and International Society for Cellular Therapy (ISCT) criteria to determine the purity of the lineage. Results: The explant cultured cells fulfil the defining criteria by ISCT. Further, they form colony and RT-PCR confirmed the presence of thy-1, endoglin and β-actin. The incubated explant shows successful cells migration after transferring from one culture plate to another for five consecutive times. Further, it was seen that the migrated cells can be cultured for more than 18 passages. However, a reduction was seen in the migration of the cells after the 3rd transfer of the explants. Conclusion: This study found that the transferred explant has the potential to yield cells for 5 consecutive explant transfers. Further, this technique optimized the yield of primary cells and thereby reducing the quantity and frequency of sample collection, processing time and cost.